Rhizobia selection for Al and low pH tolerance - Brose, Edemar (Pesquisa Agropecuaria Brasileira, 1991)
Under laboratory conditions, 35 Rhizobium leguminosarum bv. trifolii strains were tested as to their tolerance to Al and to low pH. In glasshouse, ten strains were tested in a Brown Latosol Dystrophic soil in two pH levels (6.0 and 5.0). Rhizobia growth was more limited by Al than by the low pH, but the Al-tolerant strains did not differ between 75 and 150 <span style="line-height: 115%; font-family: ";Calibri";,";sans-serif";; font-size: 13.5pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-ansi-language: PT-BR; mso-bidi-language: AR-SA;">µM of Al in the pH 4.5. When the pH was reduced from 6.5 to 4.7, the total number of nodules reduced in 70% and the large nodules in 50%. The dry matter (DM) yield, as general mean, was slightly higher in the pH 6.5. In nutrient solution, with pH 4.7+Al, six strains were 22 to 43% higher than the controls SEMIA 222 and 235 on DM yield. In soil, the strain EEL 7882 was superior in 6% on DM and in 10% on TN to the control SEMIA 235. In the pH 5.0 the strain EEL 1285 and EEL 8186 were higher in 34% and 37% on DM, and in 37% and 39% on TN than the control, respectively.